Automatic operation of the optical system in the theatrical show (Al-Academy, 2023)
Theatrical techniques took upon themselves the responsibility of building and organizing the theatrical form for the various forms of performances, and it was the important tool that the show makers could rely on in carrying out the various works at the audio-visual level, and lighting is one of the most important elements of the visual formation of the image in the show, as it is related to the visual process and what it can achieve in operations The contrast that constitutes the aesthetic and intellectual values of the theatrical show, especially since the process of adjusting the element of time and the timings for receiving or delivering, moving, and the movement of the actor is what can determine the rhythm of the scene, which in its totality represents the rhythm of the show, and the processes of delay and confusion in the process of implementing various types of effects or techniques and light are the most important element that can Work to raise the aesthetic, artistic and intellectual values of the display in the case of controlling its implementation and control processes. Therefore, the researcher worked to find a simple technical and technical alternative that works to avoid these errors, accompanied by ease in the process of distribution and design of lighting and the shapes of its projections, since most of the workers now in the field of lighting design and implementation are Technicians with different specializations and far from the stage, which makes the percentage of errors received large. This device can avoid these errors that may appear inadvertently or by an executive error. For this, the researcher proposes a process of manufacturing a device that can perform lighting during the theatrical show, as a technical substitute for the lighting port, which calls for a process to reduce the percentage Errors that may occur during the theatrical show, in addition to the ease of programming and controlling it automatically, which contributes to the process of its spread in various types of theaters, even those in which there are no technicians or lighting technicians, and at a simple manufacturing cost that is not comparable to the cost of traditional control devices found in public theaters